Emulsification by TPGS or Quillaja Extract Increased Absorption and Affected Metabolism of Berberine in Humans. (7th June 2021) - Yagiz, Yavuz; Wang, Gary; Gu, Liwei
Abstract: Objectives: Berberine is a botanical alkaloid used widely for the prevention of several diseases. However, the absorption rate of berberine is less than 1% in human. The objectives of this study were to determine whether emulsification by TPGS or Quillaja extract affect the absorption and metabolism of orally ingested berberine in human volunteers. Methods: Twelve healthy subjects (7 male and 5 females, 21–50-year-old) participated this study. Each subject received 800 mg berberine in a powder form or emulsified with TPGS or Quillaja extract using a randomized crossover design with one-week washout period. Blood samples were collected at 0, 0.5, 1, 2, 3, 4, 6, 8, and 12 hours after dose. Plasma was hydrolyzed with glucuronidase and sulfatase before total content of berberine and its metabolites were analyzed on LC/MS/MS. Free forms of metabolites were determined in plasma without hydrolysis. Pharmacokinetic parameters were calculated using a non-compartment model before they were compared by analysis of covariance. Results: The area under the curve (AUC) and peak plasma concentration (Cmax) of berberine was 6.6 μM.hr and 0.9 μM in participants received berberine powder. They were increased to 18.3 μM.hr and 4.5 μM by TPGS emulsification and 28 μM.hr and 5.1 μM by Quillaja extract emulsification, respectively. Berberrubine and demethylberberine were major metabolites of berberine. The AUC of free Berberrubine and demethylberberine was increased by 1.9 fold and 1.6 fold by TPGS and 5.9 folds and 2.7 folds by Quillaja extract, respectively, compared to berberine powder. Participants received berberine powder had AUC of 254 μM.hr and Cmax of 33 μM for total berberrubine. TPGS emulsification increased these values to 425 μM.hr and 54 μM, while Quillaja extract increased them to 341 μM.hr and 44 μM, respectively. Significant increases of AUC and Cmax were also observed for total demethylberberine by TPGS or Quillaja extract emulsification. Conclusions: Emulsification of berberine with TPGS or Quillaja extract significantly increased the absorption of berberine and its metabolites in human compared to berberine supplement without emulsifiers. Funding Sources: Florida High Tech Corridor Council and Designs for Health.